A case of intravascular lymphoma diagnosed in an explanted liver after liver transplantation. (8th June 2015) - Kuramitsu, Kaori; Fukumoto, Takumi; Yano, Yoshihiko; Hirano, Hirotaka; Misumi, Takuyo; Katayama, Yosio; Kawano, Hiroki; Yakushijin, Kimikazu; Zen, Yoh; Itoh, Tomoo; Ku, Yonson
Summary Intravascular lymphoma (IVL) is a rare form of B‐cell lymphoma. We encountered a rare case of IVL diagnosed in an explanted liver. A 49‐year‐old man visited a clinic with high fever. Because of elevated liver function, he was diagnosed with acute liver failure. Deceased donor liver transplantation (LT) was performed 16 days after admission. The post‐transplantation course was uneventful until IVL was reported in the explanted liver on postoperative day (POD) 21. Rituximab was administered on POD 27, and rituximab–cyclophosphamide, hydroxydaunorubicin, oncovin, prednisone (R‐CHOP) treatment administered on POD 38. The R‐CHOP treatment was repeated for eight cycles, and the patient remains free of recurrence 1 year post‐transplantation. Although systemic lymphoma is a contraindication to transplantation, our experience indicates that IVL can be successfully treated by the administration of prompt chemotherapy after LT for fulminant hepatitis.